Book review: Ellison, S. H. 2018: Domesticating Democracy: The Politics of Conflict Resolution in Bolivia. (October 2019) - Iyer, Soundarya
Ellison, S. H. 2018: Domesticating Democracy: The Politics of Conflict Resolution in Bolivia . Durham and London: Duke University Press. 296 pp. US$99.95 (Cloth), US$26.95 (Paperback). ISBN: 978-0-8223-7093-2 (Cloth), 978-0-8223-7108-3 (Paperback).